PENTINGNYA EDUKASI KEUANGAN KELUARGA - Widyartono, Agustinus; Kewal, Suramaya Suci; Putranto, Yohanes Andri; Mendari, Anastasia Sri; Heriyanto, Heriyanto (Universitas katolik Musi Charitas, 2021)
Community Service Activities are carried out by the team and partners in an online form using zoom. The zoom link is prepared by the partner. Providing material on